2011
DOI: 10.1007/s11661-011-0685-0
|View full text |Cite
|
Sign up to set email alerts
|

Selective Oxidation and Reactive Wetting during Galvanizing of a CMnAl TRIP-Assisted Steel

Abstract: A transformation induced plasticity (TRIP)-assisted steel with 0.2 pct C, 1.5 pct Mn, and 1.5 pct Al was successfully galvanized using a thermal cycle previously shown to produce an excellent combination of strength and ductility. The steel surface chemistry and oxide morphology were determined as a function of process atmosphere oxygen partial pressure. For the 220 K (-53°C) dew point (dp) + 20 pct H 2 atmosphere, the oxide morphology was a mixture of films and nodules. For the 243 K (-30°C) dp + 5 pct H 2 at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
30
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(33 citation statements)
references
References 39 publications
3
30
0
Order By: Relevance
“…[13][14][15][16][17] Samples comprised 120 mm 9 200 mm sheets such that the rolling direction (RD) was parallel to the longitudinal axis of the sample. A uniform temperature area of 180 mm 9 90 mm is centered on the sample panel and only material from this area was analyzed.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…[13][14][15][16][17] Samples comprised 120 mm 9 200 mm sheets such that the rolling direction (RD) was parallel to the longitudinal axis of the sample. A uniform temperature area of 180 mm 9 90 mm is centered on the sample panel and only material from this area was analyzed.…”
Section: Methodsmentioning
confidence: 99%
“…Previous work by the research group of the present authors and others has shown that high quality galvanized coatings can be obtained for TRIP-assisted steels in which Si was either partially or completed replaced by Al. [5][6][7][8][9][10][11][12][13][14][15][16] In particular, the present authors have successfully coated two high Al, low Si (0.20C-1.5Mn-1.0Al-0.5Si and 0.20C-1.5Mn-1.5Al (wt pct)) steels [14][15][16] for which very good mechanical properties were also obtained. [17] A further challenge of processing TRIP-assisted steels within the CGL concerns the thermal cycles commonly used.…”
Section: Jr Mcdermid Hs Zurob and Y Bianmentioning
confidence: 99%
“…One of the methods was the application of inorganic coatings [5][6][7][8] such as Alxwt.%Si (x = 0~31.9) coatings [9][10][11][12], Zinc silicate coatings [13] and zinc coatings [14,15].…”
Section: A N U S C R I P Tmentioning
confidence: 99%
“…Mn, Cr, Si, Al) in AHSS have a higher affinity to oxygen than iron, leading to the formation of oxides of these elements during the annealing process prior to galvanizing. The presence of these alloying element oxides at the steel surface reduces the zinc wettability [3] and thus impairs the galvanizing quality [4]. Therefore, it is imperative to understand the oxidation behaviour of AHSS in N 2 plus H 2 gas mixtures with various dew points and to find conditions to mitigate the formation of external oxides after annealing.…”
Section: Introductionmentioning
confidence: 99%